Performance of Cocoa Graft Seedlings as a Result of Different Number of Lower Stem Leaves and Entry Defoliation Time - Mismawarni Srima Ningsih; Syafrison Syafrison; Fardedi Fardedi; Giska Oktabriana; Mela Rahmah; Hary Yanto Jailani; Mukhlis Mukhlis (Postgraduate, University of Mataram, 2024)
This research aims to see the effect of the number of leaves left on the rootstock and the best defoliation time to improve the performance of cacao shoot connection seedlings. The research was conducted in the experimental garden of Politeknik Pertanian Negeri Payakumbuh from March to July 2023. Cocoa clone ICS was used as rootstock and clone TSH as scion. The experimental design was 4x4 factorial with 3 replications, the environmental design was completely randomized design. Data were analyzed statistically using F test and DNMRT further test at 5% level. From the research and data processing, it was found that there is an interaction between the treatment of different number of rootstock leaves and different defoliation times on the performance of cocoa shoot grafting seedlings based on the variables of percentage of grafted seedlings, number of shoots, number of leaves, leaf area and weight of seedling scion. It can be concluded that defoliation of the rootstock six days before splicing with rootstock having four leaves produces the best performance of cacao shoot grafting seedlings